Evaluation of a Novel Structural Adhesive for the Automotive Industry - J. P. R. Monteiro; R. D. S. G. Campilho (Techniques and Innovation in Engineering Research and Technology Vol. 5, 2023)
High performance structural adhesives are currently being used more frequently in the automobile sector to decrease vehicle weight and improve the crash resistance of automotive structures. The high performance adhesives used in the automobile sector must be able to endure heavy dynamic loads in addition to having high mechanical strength in order to meet these requirements. Because of their complicated behaviour, the design process required to create structures with these materials necessitates a thorough understanding of their mechanical properties. In this work, the mechanical properties of a structural epoxy, Sikapower® 4720, were determined. Tensile tests were performed to determine the Young’s modulus (E) and tensile strength (\(σ\)f). Shear tests were performed to determine the shear modulus (G) and the shear strength (\(τ\)f). Tests were also carried out to determine the adhesive’s toughness. For mode I toughness determination (GIc), the Double-Cantilever Beam (DCB) test was employed. For determination of toughness under mode II (GIIc), the End-Notched Flexure (ENF) test was performed. The test findings were able to thoroughly mechanically define the adhesive and show that it not only has strong mechanical strength but also a high degree of ductility.